Pertumbuhan Padi Sawah dengan Perlakuan Biomatriconditioning Benih dan Umur Bibit Pindah Tanam Mensimulasikan Metode Tanam SRI - Rismiati Rismiati; La Ode Afa; Nini Mila Rahni (LP3M Universitas Muhammadiyah Kendari, 2023)
This research aims to evaluate the effects of biomatriconditioning treatment of seeds and the age of seedlings at transplanting on the growth of paddy rice, simulating the System of Rice Intensification (SRI) method. The study employs a Split Plot design within a Randomized Complete Block Design (RCBD) with 3 replications. The primary focus is on seeds subjected to six biomatriconditioning treatments: untreated seeds (B1 and B2), treatment with red brick powder (B3 and B5), and treatment with rice husk charcoal powder (B4 and B6). The age of seedlings at transplanting is categorized into four levels: direct planting (H0), 7 days (H1), 14 days (H2), and 21 days (H3). Observed parameters encompass plant height, leaf count, tiller count, leaf area, and Relative Growth Rate (RGR). Analysis results indicate an optimal interaction at B6H1, displaying the tallest plant height, while the highest leaf count is achieved at B2H1. Maximum leaf area is attained at B4H3, and the highest tiller count is found in B5H2. The most effective treatment for RGR is transplanting after 21 days (H3), with the optimal biomatriconditioning treatment being B4. These findings suggest that the application of rice husk charcoal powder with Bacillus sp. PLK7 on 21-day-old seedlings holds the potential to significantly enhance paddy rice growth, aligning with the SRI method.